Effects of insulin on sperm cell quality in ram semen cooled at 5°C - Maurício Fraga van Tilburg; Rodrigo Vasconcelos de Oliveira; Carla Renata Figueiredo Gadelha; Bruno Fagundes; Angelo Jose Burla Dias; Célia Raquel Quirino; José Frederico Straggiotti Silva (Semina: Ciências Agrárias, 2021)
Insulin is present in the seminal plasma and is involved in sperm activities like motility and capacitation. However, the effects of insulin on the viability of cooled ram sperm are not fully understood. Therefore, the objective of the current study was to evaluate the effect of insulin addition on ram sperm maintained at 5ºC. Sperm samples were collected from six healthy, mature Santa Inês rams. The ejaculates were divided into two aliquots with (insulin group) or without (control group) insulin (3 IU mL-1) in the semen extender, and then cooled at 5°C for 48 hours. Subsequently, the sperm cells were evaluated for motility and kinetics using computer-assisted semen analysis. The samples were evaluated for acrosomal integrity by fluorescein using isothiocyanate combined with peanut agglutinin (FITC-PNA) and membrane functionality by the hypoosmotic swelling test. The semen analysis was performed after 24 or 48 hours of cooling. There was an increased percentage of progressive sperm motility (%), straightness (%), linearity (%) and beat caudal frequency (Hz) in the insulin group after 24 and 48 hours of cooling (p < 0.05). However, insulin did not affect total sperm motility, sperm velocities (VSL, VAP and VCL) (µm seg-1), acrosomal integrity and membrane functionality during cooling (p > 0.05). In conclusion, the addition of 3 IU mL-1 insulin to ram semen extender improved the quality of sperm motility after cooling.